PROTECTION OF FOOD GROWING LAND IN LAND ACQUISITION FOR PUBLIC INTEREST - Ade Arif Firmansyah; Malicia Evendia; Budiyono Budiyono (Law Faculty of Universitas Bandar Lampung, 2026)
Infrastructure development has resulted in a decline in rice paddy area, rice production, and rice yields. The harvested rice area in 2024 decreased by 167.57 thousand hectares compared to 2023. This resulted in a decline in rice production in 2024, which amounted to 838.27 thousand tons compared to 2023. This shrinking agricultural land requires model protection of sustainable food agricultural land within the legal framework of land acquisition for public interest. This paper aims to offer a model protection of sustainable food agricultural land in land acquisition law for public interestso it is hoped that it will be able to guarantee protection sustainable food agricultural land and supports the achievement of food security and sovereignty. Using the doctrinal writing method with a conceptual approach and statutory regulations, it was found that: model Protection of sustainable food agricultural land in land acquisition law for public interest is composed of two important aspects, namely planning and institutional coordination. Where these two aspects are things that must be accommodated in change of Law Number 2 of 2012 concerning Land Acquisition for Development in the Public Interest.